What do we mean when we talk about trust in social media? A systematic review - Zhang, Yixuan; Gaggiano, Joseph D.; Yongsatianchot, Nutchanon; Nurul Mubinah, Suhaimi; Kim, Miso; Sun, Yifan; Griffin, Jacqueline A.; Parker, Andrea Grimes (2023)
Do people trust social media? If so, why, in what contexts, and how does that trust impact their lives? Researchers, companies, and journalists alike have increasingly investigated these questions, which are fundamental to understanding social media interactions and their implications for society. However, trust in social media is a complex concept, and there is conflicting evidence about the antecedents and implications of trusting social media content, users, and platforms. More problematic is that we lack basic agreement as to what trust means in the context of social media. Addressing these challenges, we conducted a systematic review to identify themes and challenges in this field. Through our analysis of 70 papers, we contribute a synthesis of how trust in social media is defined, conceptualized, and measured, a summary of trust antecedents in social media, an understanding of how trust in social media impacts behaviors and attitudes, and directions for future work.